The New Waqf Institution in Indonesia - Muhammad Syaifuddien Zuhriy (Quality Assurance Institute (LPM) State Islamic University Walisongo Semarang, 2015)
Waqf as religious institution has applicative functions for all moeslems. Since its coming in Indonesia, Waqf had been already performed by ummat for supporting its spread. Even, until now, we can find that many Islamic religious building were constructed on the Waqf assets. For Moeslems, performing waqf as charity action, on the side, become a evidence the high awareness of their adherence to Allah SWT. Therefore, this religious donations practice often was stated that it is not only function as the reflection of personal loyalty to Allah but also function as completion to the social necessities. In Indonesia, its existence is paid serious attention by government. The shape of attention has already come up with the series of some positive regulations. In sociology perspective, this condition brings out new social institution in society, particularly religious institution. So, the institution with its regulative function is expected to be able to complete the less of available religious regulation and to protect the amazing potency of waqf assets. Of course, to carry out this mission needs long period and also strong efforts, mainly everyone who care with this goal and moreover, Government.Because of that, this article will elaborate this problem, including how to institutionalize and internalize the new institution. Because, the new institution will work effectively while has already passed the process. It means the strategic to do that becomes the essential step to encourage the new institution, namely Waqf as religious institution.